1908 Vt. Acts & Resolves 132-33, No. 147, § 1 - (:unkn) unknown (My University, 1908)
No person shall at any time hunt, shoot, pursue, take or kill any of the wild animals, wild fowl or birds of this state, nor use a gun for hunting the same, without having first procured a license therefor as hereinafter provided, and then only during the respective periods of the year when it shall be lawful, and subject to all the provisions of chapter 220 of the Public Statutes
Keywords: HUNTING REGULATION